The Impact of Political Corruption on Socio-Economic Development in Nigeria - Tochukwu Ezeudu (Journal of Public Administration and Government, 2023)
This study investigates the relationship between political corruption and socio-economic development in Nigeria using a mixed-methods approach. Descriptive statistics, regression analysis, and inferential statistics are employed to analyze data collected from diverse participants, including government officials, policymakers, economists, civil society representatives, and citizens. The findings reveal key indicators of socio-economic development and demonstrate that political corruption negatively impacts GDP growth, while education expenditure and infrastructure investment have positive effects. The study highlights the importance of addressing corruption, increasing investments in education and infrastructure, and implementing anti-corruption measures to foster sustainable development in Nigeria. These findings provide valuable guidance for policymakers in formulating evidence-based strategies to promote inclusive economic growth and combat corruption.